Supply chain modeling in assembly production - Leinonen, Ville (My University, 2017)
In modern, constantly changing, global market economy it is important for companies to continuously develop their own operations and maintain competitive strength. It is important to be able to increase customer satisfaction and create positive difference to the competitors, which are usually resulting from successful continuous improvement and development process. Nowadays developing only company’s own processes is not solely enough. It is also important to examine how processes work in the supply chain, outside of company’s own organization. While companies concentrate their resources more and more only on their core competencies, the impact of the suppliers as part of the company’s processes and success increases significantly. Thus, it is important to improve and develop the supply chain also outside company’s own organizations. Achieving high customer satisfaction usually requires competitive delivery times and high quality products among other things. Subject company operates in a business where customer lead times are a high priority when choosing deliverer. Furthermore, annual product-specific demand fluctuations are high. For these reasons, the delivery times promised to the customer are often much shorter than the actual production times. Because the company assembles products only against customer order, it has no finished goods inventory. This means that it has both component and raw material inventories located along the supply chain. Due to the high demand fluctuations, the material / inventory management creates challenges to the supply chain. The purpose of this thesis is to find solutions to above-mentioned challenges and provide development suggestions for process improvements. The goal is to find a competent model to help manage safety stock levels and present development ideas to improve cooperation between different stakeholders of the supply chain. Thesis also covers different aspects and requirements of inventory management. For example, is it possible to turn over the management of certain inventories to suppliers and give them access to company’s demand data, instead of managing the inventories internally and sending purchase orders to suppliers when inventory levels demand for it. The data used in this thesis is from subject company’s own demand and consumption data and component suppliers corresponding data. The data is from 2016, because it represents well the annual demand curve.

Nykyajan alati muuttuvassa globaalissa markkinataloudessa yritysten on tärkeää pyrkiä jatkuvasti kehittämään omaa toimintaa ja ylläpitämään kilpailukykyä. Asiakastyytyväisyyden kasvattaminen ja kilpailijoista positiivisesti erottuminen ovat tärkeitä asioita, jotka ovat yleensä seurausta onnistuneesta jatkuvasta toiminnan ja prosessien kehittämisestä. Nykyään pelkästään yrityksen sisäisten toimien kehittäminen ei enää riitä vaan on tärkeää katsoa asiaa myös koko toimitusketjun kannalta. Yritysten keskityttyä yhä enemmän pelkästään omaan ydinosaamiseensa, alihankkijoiden ja toimitusketjun rooli osana yrityksen menestystä kasvaa. Näin ollen toimitusketjua kannattaa kehittää ja huomioida myös oman organisaation ulkopuolella. Korkean asiakastyytyväisyyden saavuttaminen edellyttää yleensä muun muassa kilpailukykyisiä toimitusaikoja sekä asiakkaan tarpeita vastaavia laadukkaita tuotteita. Kohdeyrityksen toimialalla tuotteiden saatavuusaika on asiakkaille tärkeä kriteeri toimittajaa valitessa ja tuotekohtaiset kausivaihtelut ovat suuria. Tämän vuoksi yrityksen lupaamat toimitusajat joidenkin tuotteiden kohdalla ovat huomattavasti lyhyempiä kuin mikä varsinainen kokonaisvalmistusaika on. Koska yritys ei pidä minkäänlaista valmisvarastoa, vaan kaikki tuotteet kootaan vain asiakastilausta vastaan, täytyy toimitusketjun varrella olla sekä raakamateriaali- että komponenttivarastoja. Suurien kysyntävaihteluiden takia varastojen hallinnassa muodostuu haasteita. Tämän diplomityön tarkoitus on etsiä ratkaisuja edellä mainittuihin haasteisiin ja antaa kehitysehdotuksia toiminnan kehittämiseen. Tavoitteena on löytää toimintakelpoinen malli auttamaan varmuusvarastotasojen määrittämisessä sekä löytää kehitysideoita yhteistyön parantamiseksi eri sidosryhmien välillä. Työssä käsitellään myös varastonhallinnan eri mahdollisuuksia ja niiden vaatimuksia, onko mahdollista antaa tiettyjen komponenttivarastojen hallintavastuu suoraan toimittajalle ja antaa toimittajalle pääsy kysyntätietoihin vai edelleen itse hallinnoida varastoja ja lähettää ostotilaukset toimittajille normaaliin tapaan. Työssä materiaalina on käytetty kohdeyrityksen tuottamaa omaa kysyntä- ja kulutusaineistoa sekä komponenttitoimittajien vastaavaa aineistoa. Referenssivuotena on käytetty vuotta 2016, koska kyseisen vuoden aineisto on ehjä ja kuvaa erittäin hyvin kysyntäkäyttäytymistä vuosittain.
Toimitusketjun mallintaminen kokoonpanoteollisuudessa
Keywords: supply chain; supply chain management; sales and operations planning; safety stock